Life-Stage Dependent Plasticity in the Auditory System of a Songbird Is Signal and Emitter-Specific - Adreani, Nicolas M.; D’Amelio, Pietro B.; Gahr, Manfred; ter Maat, Andries (Frontiers in Neuroscience, 2020)
Social animals flexibly use a variety of vocalizations to communicate in complex and dynamic environments. However, it remains unknown whether the auditory perception of different vocalizations changes according to the ecological context. By using miniature wireless devices to synchronously record vocal interactions and local neural activity in freely-behaving zebra finches in combination with playback experiments, we investigate whether the auditory processing of vocalizations changes across life-history stages. We show that during breeding, females (but not males) increase their estrogen levels and reply faster to their mates when interacting vocally. These changes are associated with an increase in the amplitude of the female’s neural auditory responses. Furthermore, the changes in auditory response are not general, but specific to a subset of functionally distinct vocalizations and dependent on the emitter’s identity. These results provide novel insights into auditory plasticity of communication systems, showing that the perception of specific signals can shift according to ecologically-determined physiological states.